Formação inicial de professores: uma análise dos cursos de licenciatura em química das universidades públicas do estado de São Paulo - Kasseboehmer, Ana Cláudia (Universidade Federal de São Carlos, 2006)
This work aimed to analyze the process of reformulation/creation of Teaching Courses in Chemistry of public universities of São Paulo to attend the new legislation. It was also observed the engagement of professors and students staffs in this initial forming process, looking at the reflexive paradigm of Donald A. Schön. The gathering of data in this qualitative research consisted in analyzing pedagogical projects and curriculum matrix of courses before and after that reformulation, as well as in interviewing personally coordinators of courses, teachers of the older subject Teaching Practice in Chemistry and Supervised Stage and three students of the conclusion year in nine different courses in the state. It was observed that this process of reformulation/creation occurred with a low involvement of the professors; in addition, in a general way, we can say that exist a strong diverse treatment related to these courses and the teaching occupation, diminishing them if compared to bachelorship course and researching activities. Excepting isolated cases, the professor staff of those courses demonstrates a low preoccupation with his teaching activity as well as to educate his students to become teachers according to the reflexive professional model. The activities of Teaching Practice as a Curriculum Component and Curriculum Stage are not detailed in some pedagogical projects, to the point that some coordinators do not know the nature of these activities or facts, such as, for example, the observing classes as a kind of stage is not relevant as a formative experience in the students opinion. There is a significant detachment among the units that teach the Chemistry and Pedagogical subjects as well as among the University and High School, that injured the forming of Chemistry good teachers. It was noticed to be necessary (and urgent) institutional changes in the direction of requiring that the professors be dedicated in equal responsibility to teaching activity, as occurs concerning to research.
Initial forming of teachers: an analysis of teaching courses in chemistry of public universities of São Paulo estate
Keywords: Química - ensino; Prática de ensino; Professores - formação; Avaliação de curso; Planejamento de ensino - projeto político pedagógico; CIENCIAS EXATAS E DA TERRA::QUIMICA